Pemanfaatan Aplikasi Mobile untuk Pencatatan Keuangan pada Usaha Banten di Bhuana Asri Dalung - Rosalia Hadi; I Gede Nika Wirawan; I Gusti Ngurah Ady Kusuma; Ni Luh Gede Pivin Suwirmayanti (Journal of Community Development, 2021)
Banten is a tool offered by Hindus as a form of gratitude to God Almighty for his bestowed blessings. Every Hindu family is obliged to provide Banten as a means of daily religious ceremonies. Therefore people who can make Banten are needed to meet these needs. That is what prompted Mrs Kadek Suli to open this business. Mrs Kadek Suli's offering business is located at Br. Bhuana Asri Dalung, North Kuta District, Badung Regency. The business, which was started in 2015, provides various Banten needs, such as Canang, Meghan, Sodaan, etc. This service activity aims to help Mrs Kadek Suli know the profit/loss of her business and add to Mrs Kadek Suli's insight regarding the use of mobile applications other than for entertainment, namely Mrs Kadek Suli can also use it for financial records and making monthly reports, Mrs Kadek Suli never takes notes the amount of income or expenditure, so you do not know the profit/loss of the business. Through this service activity, Mrs Kadek Suli can use a mobile application to record her daily income and expenses and make monthly reports, so that you can find out the profit/loss from her business. The stages of this service activity began with outreach to partners about the importance of information technology and financial recording, then continued with a training stage in Android-based financial applications to record income and expenditure and make monthly reports. The final stage of the activity is monitoring and evaluation. The results obtained from this activity are that now Mrs Kadek Suli knows the use of information technology and can use mobile applications for financial recording and monthly reports.